K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

11 tháng 12 2018

\(x^2-2xy+y^2-z^2=\left(x-y\right)^2-z^2=\left(x-y-z\right)\left(x-y+z\right)\)

\(3x^2+6xy+3y^2-3z^2=3\left(x^2+2xy+y^2-z^2\right)=3.\left[\left(x+y\right)^2-z^2\right]=3.\left(x+y-z\right)\left(x+y+z\right)\)

\(3x^2-3xy-5x+5y=3x\left(x-y\right)-5\left(x-y\right)=\left(x-y\right)\left(3x-5\right)\)

11 tháng 12 2018

a)\(x^2-2xy+y^2-z^2=\left(x-y\right)^2-z^2=\left(x-y+z\right)\left(x-y-z\right)\)

b)\(3x^2+6xy+3y^2-3z^2=3\left[\left(x+y\right)^2-z^2\right]=3\left(x+y+z\right)\left(x+y-z\right)\)

c)\(3x^2-3xy-5x+5y=3x\left(x-y\right)-5\left(x-y\right)=\left(3x-5\right)\left(x-y\right)\)

20 tháng 4 2017

Bài giải:

a) x2 + 4x – y2 + 4 = (x2 + 4x + 4) - y2

= (x + 2)2 – y2 = (x + 2 – y)(x + 2 + y)

b) 3x2 + 6xy + 3y2 – 3z2 = 3[(x2 + 2xy + y2) – z2]

= 3[(x + y)2 – z2] = 3(x + y – z)(x + y + z)

c) x2 – 2xy + y2 – z2 + 2zt – t2 = (x2 – 2xy + y2) – (z2 – 2zt + t2)

= (x – y)2 – (z – t)2

= [(x – y) – (z – t)] . [(x – y) + (z – t)]

= (x – y – z + t)(x – y + z – t)

2 tháng 6 2017

48. Phân tích các đa thức sau thành nhân tử:

a) x2 + 4x – y2 + 4; b) 3x2 + 6xy + 3y2 – 3z2;

c) x2 – 2xy + y2 – z2 + 2zt – t2.

Bài giải:

a) x2 + 4x – y2 + 4 = (x2 + 4x + 4) - y2

= (x + 2)2 – y2 = (x + 2 – y)(x + 2 + y)

b) 3x2 + 6xy + 3y2 – 3z2 = 3[(x2 + 2xy + y2) – z2]

= 3[(x + y)2 – z2] = 3(x + y – z)(x + y + z)

c) x2 – 2xy + y2 – z2 + 2zt – t2 = (x2 – 2xy + y2) – (z2 – 2zt + t2)

= (x – y)2 – (z – t)2

= [(x – y) – (z – t)] . [(x – y) + (z – t)]

= (x – y – z + t)(x – y + z – t)

19 tháng 7 2019

a) \(x^2+4x-y^2+4\)

\(=\left(x+2\right)^2-y^2\)

\(=\left(x+2-y\right)\left(x+2+y\right)\)

19 tháng 7 2019

c) \(x^2-2xy+y^2-z^2+2zt-t^2\)

\(=\left(x-y\right)^2-\left(z-t\right)^2\)

\(=\left(x-y-z+t\right)\left(x-y+z-t\right)\)

11 tháng 12 2018

\(x^2+5x+6\)

\(=x^2+3x+2x+6\)

\(=x.\left(x+3\right)+2.\left(x+3\right)=\left(x+3\right).\left(x+2\right)\)

5 tháng 7 2021

a.\(xz+yz-5\left(x+y\right)\)

\(=z\left(x+y\right)-5\left(x+y\right)\)

\(=\left(x+y\right)\left(z-5\right)\)

b.\(3x^2-3xy-5x+5y\)

\(=3x\left(x-y\right)-5\left(x-y\right)\)

\(=\left(x-y\right)\left(3x-5\right)\)

c.\(x^2+6x-y^2-3z^2\)???Sai đề bài ...?

d.\(3x^2+6xy+3y^2-3z^2\)

\(=3\left(x^2+2xy+y^2-z^2\right)\)

\(=3\left[\left(x+y\right)^2-z^2\right]\)'

\(=3\left(x+y-z\right)\left(x+y+z\right)\)

5 tháng 7 2021

Trả lời:

a, xz + yz - 5 ( x + y )

= ( xz + yz ) - 5 ( x + y )

= z ( x + y ) - 5 ( x + y )

= ( x + y ) ( z - 5 )

b, 3x2 - 3xy - 5x + 5y

= ( 3x2 - 3xy ) - ( 5x - 5y )

= 3x ( x - y ) - 5 ( x - y )

= ( x - y ) ( 3x - 5 )

c, x2 + 6x - y2 - 3z2

= - ( 3x2 - x2 + y2 - 6x )

d, 3x2 + 6xy + 3y2 - 3z2

= 3 ( x2 + 2xy + y2 - x2 )

= 3 [ ( x2 + 2xy + y2 ) - z2 ]

= 3 [ ( x + y )2 - z2 ]

= 3 ( x + y - z ) ( x + y + z )

Câu 2 nha

\(a,x^4+2x^3+x^2\)

\(=x^2\left(x^2+2x+1\right)\)

\(=x^2\left(x+1\right)^2\)

\(c,x^2-x+3x^2y+3xy^2+y^3-y\)

\(=\left(x^3+3x^2y+3xy^2+y^3\right)-\left(x+y\right)\)

\(=\left(x+y\right)^3-\left(x+y\right)\)

\(=\left(x+y\right)\left(x^2+2xy+y^2-1\right)\)

19 tháng 6 2015

b)x2+2xy+y2-16=(x+y)2-42=(x+y+4)(x+y-4)

c)3x2+5x-3xy-5y=x(3x+5)-y(3x+5)=(3x+5)(x-y)

d)4x2-6x3y-2x2+8x=2x(2x-3x2y-x+4)

e)x2-4-2xy+y2=(x2-2xy+y2)-4=(x-y)2-22=(x-y-2)(x-y+2)

k)x2-y2-z2-2yz=x2-(y+z)2=(x-y-z)(x+y+z)

m)6xy+5x-5y-3x2-3y2=3(x2-2xy+y2)+5(x-y)=3(x-y)2+5(x-y)=(x-y)(3x-3y+5)


 

27 tháng 6 2016

b. (x^2+2xy+y^2)-16 =(x+y)^2-16=(x+y+4)(x+y-4)

11 tháng 10 2017

1)

a) \(x^2-xy+x-y=x\left(x-y\right)+\left(x-y\right)=\left(x-y\right)\left(x+1\right)\)

b) \(xz+yz-5\left(x+y\right)=z\left(x+y\right)-5\left(x+y\right)=\left(x+y\right)\left(z-5\right)\)

c) \(3x^2-3xy-5x+5y=\left(3x^2-3xy\right)-\left(5x-5y\right)=3x\left(x-y\right)-5\left(x-y\right)=\left(x-y\right)\left(3x-5\right)\)

11 tháng 10 2017

Bài 2:

a) \(x^2+4x-y^2+4=\left(x^2+2\cdot x\cdot2+2^2\right)-y^2=\left(x+2\right)^2-y^2=\left(x-y+2\right)\left(x+y+2\right)\)

b) \(3x^2+6xy+3y^2-3z^2=3\left(x^2+2xy+y^2-z^2\right)=3\left[\left(x+y\right)^2-z^2\right]=3\left(x+y-z\right)\left(x+y+z\right)\)

c) \(x^2-2xy+y^2-z^2+2zt-t^2=\left(x-y\right)^2-\left(z-t\right)^2=\left(x-y-z+t\right)\left(x-y+z-t\right)\)